2019
DOI: 10.3390/nu11102338
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Early Childhood and Later Childhood Sugar-Containing Beverage Intake: A Prospective Cohort Study

Abstract: Sugar-containing beverages (SCBs) are a major source of sugar intake in children. Early life intake of SCBs may be a strong predictor of SCB intake later in life. The primary objective of this study was to evaluate if SCB intake (defined as 100% fruit juice, soda, and sweetened drinks) in early childhood (≤2.5 years of age) was associated with SCB intake in later childhood (5–9 years of age). A prospective cohort study was conducted using data from the TARGet Kids! primary care practice network (n = 999). Typi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…In addition, based on the data collected in a previous study between 2013 and 2018, the beverages in China had the highest median total sugar content as compared with many other countries, such as Australia, Canada, Chile, the UK, and the USA [ 13 ]. The existing evidence suggests that the intake of SSBs in early childhood was significantly associated with higher SSB intake later in life [ 14 ]. Therefore, it is urgent to take effective measures to alter this situation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, based on the data collected in a previous study between 2013 and 2018, the beverages in China had the highest median total sugar content as compared with many other countries, such as Australia, Canada, Chile, the UK, and the USA [ 13 ]. The existing evidence suggests that the intake of SSBs in early childhood was significantly associated with higher SSB intake later in life [ 14 ]. Therefore, it is urgent to take effective measures to alter this situation.…”
Section: Introductionmentioning
confidence: 99%
“…A introdução alimentar precoce de bebidas açucaradas é um dos muitos fatores biológicos, sociais e ambientais que permanecem sendo umas das principais influências gustativas ao longo da vida, e principal desencadeador de excesso de peso infantil. O consumo exagerado de produtos industrializados, assim como a ausência de incentivo dos pais para o consumo de alimentos mais naturais, a falta de informação e o comodismo, são fatores que influenciam os hábitos alimentares das crianças, favorecendo de uma forma negativa para a saúde na infância (CHICONATTO; DA SILVA; BENINCA; SCHMITT, 2019;ARPINI et al, 2014;ZIESMANN et al 2019).…”
Section: Resultsunclassified
“…A associação entre a ingestão dessas bebidas e obesidade pode estar correlacionada com o elevado teor de açúcar, a ausência de micronutrientes e a baixa capacidade de saciedade deste tipo de bebida em comparação com outros alimentos (GONZALEZ-PALACIOS et al, 2019;ZIESMANN et al 2019).…”
Section: Resultsunclassified
“…Previous data have shown that adolescents have the highest consumption of SSB [ 41 ]. In addition, children who consume SSB early are more likely to continue consumption [ 42 ]. Moreover, it is challenging to recognize ADHD symptoms in early childhood, which may also cause diagnostic bias.…”
Section: Discussionmentioning
confidence: 99%